Denitrification in Seepage-Irrigated Vegetable Fields in South Florida - Eric H. Simonne; Benjamin Morgant (EDIS, 2005)
Seepage irrigation is the most common irrigation method in south Florida on muck and sandy soils, and consists of maintaining a water table perched on an impermeable layer. The top of the water table is typically maintained at between 18 and 24 inches deep. While drip irrigation has been gaining popularity in the last twenty years, seepage irrigation remains a very common production system in south Florida. In the field, the distinction between seepage irrigation and drip irrigation is not always clear, as in most cases, a perched water table is maintained in drip-irrigated fields. Because of the sandy soils low water-holding capacity, “true” drip irrigation (when all the water is provided by the drip tape) is rare in south Florida. This document is HS1004, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: January 2005.